China's energy-water nexus: Assessing water conservation synergies of the total coal consumption cap strategy until 2050. (15th January 2018) - Shang, Yizi; Hei, Pengfei; Lu, Shibao; Shang, Ling; Li, Xiaofei; Wei, Yongping; Jia, Dongdong; Jiang, Dong; Ye, Yuntao; Gong, Jiaguo; Lei, Xiaohui; Hao, Mengmeng; et al.
Highlights: The total coal consumption cap reduces coal output. The cap facilitates adjusting the structure of energy consumption. The cap has significant positive effects on the protection of water resources. Total coal consumption exceeds the coal mining scale constrained by total water use. A holistic approach to the challenges China faces related to water is critical. Abstract: China's coal-based energy supply inflicts destructive damage upon the ecological environment, though it has simultaneously safeguarded the rapid development of China's economy in recent decades. To promote ecological recovery and accelerate the adjustment of its industrial structure, China is poised to fully implement a total coal consumption cap through the "13th Five-year Plan" (2016–2020). This study assesses the feasibility of this strategy from the perspective of water resources, exploring and predicting outcomes from 2012 to 2050. After first measuring the water resources demands for the life-cycle of coal, this study then analyzes the destructive effects on water resources from coal production through to consumption, before finally evaluating the water conservation synergy effects under different plans for capped coal consumption. The results reveal that implementing a total coal consumption cap could reduce the adverse effects on the water resources system due to coal mining, washing, conversion, and utilization by comprehensively promoting conservation and protection of water resources. The study directly compares the two cap strategies of "behave as usual" and "reinforced total consumption control, " finding that neither of these strategies can totally satisfy China's existing requirements for water resources management. In future, China's total coal consumption will exceed the feasible scale of coal mining as restrained by total water use limits, and the required quantity of water for conversion and utilization of coal will also exceed its water use limit. Therefore, to achieve coordinated progress between the development of the coal-related industry and sustainable utilization of water resources, the Chinese government urgently needs to further reinforce total coal consumption controls and actively popularize the application of water-saving technology. In addition, the study estimates the damage to water resources due to China's coal consumption, determining the value of lost water resources per ton of coal consumption nationwide to be 52.76 yuan. If all of China's coal enterprises could apply water-preserving mining technology and make full use of mine water for production, the loss of water resources nationwide per ton of coal consumption could be lowered to 40.91 yuan. Therefore, the study advocates the combination of a market price adjustment mechanism and a macro total control strategy to maximize the synergic benefits between energy and water resources in China.